Reconceptualizing the Regulation of Sharia Savings and Financing Cooperatives: Integrating Supervision and Guarantee Systems - Miswan Ansori; Wahidullah; Zahrotun Nafisah; Abdul Djamil; Muhlis; Faiqul Hazmi (CV. Creative Tugu Pena, 2026)
Sharia Savings and Financing Cooperatives (KSPPS) constitute an essential component of Indonesia’s Islamic microfinance sector, providing Sharia-compliant financial services to micro and small economic actors. However, the regulatory framework governing KSPPS remains fragmented and predominantly administrative, offering limited financial supervision and insufficient protection for members’ funds. This regulatory condition creates structural disparities between KSPPS and other Sharia financial institutions and raises concerns regarding institutional stability and public trust. This study examines the legal position of KSPPS within Indonesia’s national legal framework and proposes a regulatory reconstruction aimed at integrating supervision and deposit guarantee mechanisms. Using a qualitative juridical-normative approach combined with institutional analysis and public policy evaluation, the research analyzes statutory regulations, ministerial policies, DSN-MUI fatwas, and existing supervisory practices. Comparative analysis with Islamic banking supervision is employed to identify regulatory gaps and best practices. The findings reveal that KSPPS are legally positioned as general cooperatives, resulting in fragmented oversight between administrative authorities and internal Sharia supervisory bodies that lack prudential and enforcement authority. Furthermore, the absence of a Sharia-based deposit guarantee scheme exposes members to financial risk and contradicts the Sharia objective of wealth protection (ḥifẓ al-māl). To address these challenges, the study proposes an integrated regulatory model that repositions KSPPS as Sharia microfinance institutions subject to risk-based, Sharia-compliant supervision and supported by a Sharia-based deposit guarantee scheme grounded in the principles of tabarru’ and ta‘āwun. This research contributes to Islamic financial regulation scholarship by offering a coherent normative and institutional framework that strengthens legal certainty, consumer protection, and the sustainability of Sharia cooperative finance.